„WOLNOŚĆ ALBO ŚMIERĆ” — PROLEGOMENA DO BADAŃ NAD TWÓRCZOŚCIĄ CZECZEŃSKIEGO BARDA TIMURA MUCURAJEWA - Pączek, Kamila (Przegląd Rusycystyczny, 2017)
The article is a preliminary study of contemporary Chechen bard Timur Mutsuraev and texts of his songs. The underground bard and active participant of the First Chechen War has become a legend and symbol of the Chechen struggle for independence and freedom. Despite strong anti-Russian and Islamic message Mutsuraev’s songs are popular not only among independence-oriented Chechens but also among Russian youth. Most of Mutsuraev’s works are patriotic war-songs glorifying national effort to defend Chechnya against Russian aggressors. The artist celebrates Chechen national symbols, myths and ethos. Mutsurayev’s songs are particular interesting subject of study in context of postcolonial theory.